2020
DOI: 10.1186/s13063-020-04579-6
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular prognosis in idiopathic sudden sensorineural hearing loss with vestibular dysfunction treated with oral or intratympanic glucocorticoids: a protocol for randomized controlled trial

Abstract: Background Idiopathic sudden sensorineural hearing loss (ISSNHL) is a rapid-onset sensorineural hearing impairment with unclear etiology and unsatisfying treatment effects. Vestibular dysfunction has been considered as a poor indicator in the clinical manifestations and prognosis of ISSNHL, which occurred in approximately 28–57% cases. Glucocorticoids, administered through oral or intratympanic way, are currently regularly and standardly applied for ISSNHL to improve the hearing outcome. However, the vestibula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…13 Compared with systemic steroids, ITSIs can deliver a higher drug concentration to the inner ear, thereby avoiding most of the side effects of oral steroids. 14 The literature findings on the therapeutic effect of ITSIs are inconsistent; various definitions of hearing recovery have been proposed, and various demographics have been examined. 15 Koltsidopoulos et al 8 reported significant hearing recovery in 31 (67.39%) of 46 patients who underwent ITSI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…13 Compared with systemic steroids, ITSIs can deliver a higher drug concentration to the inner ear, thereby avoiding most of the side effects of oral steroids. 14 The literature findings on the therapeutic effect of ITSIs are inconsistent; various definitions of hearing recovery have been proposed, and various demographics have been examined. 15 Koltsidopoulos et al 8 reported significant hearing recovery in 31 (67.39%) of 46 patients who underwent ITSI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the interpretation of vHIT results primarily relies on the gain value. Several studies have investigated the role of VOR gain in vHIT in patients with SSNHL (13)(14)(15)(16). However, there is limited research on the significance of pathologic saccades in vHIT in SSNHL.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have focused on the vestibular recovery in patients with ISSNHL and concurrent vestibulopathy, let alone discuss the influence of glucocorticoids on this vestibular recovery. Hao et al 21 have published a study protocol in 2020 to analyze the short- and long-term vestibular prognosis after ISSNHL with concurrent vertigo, while adjusting for glucocorticoid treatment strategies. This study might clarify the vestibular prognosis after concurrent vestibulopathy and sudden hearing loss.…”
Section: Discussionmentioning
confidence: 99%